How does climate exacerbate root causes of conflict in Zimbabwe? Climate Security Pathway Analysis - Ferre Garcia, Tania; Madurga-Lopez, Ignacio; Liebig, Theresa; Tarusarira, Joram; Sax, Niklas; Pacillo, Grazia; Läderach, Peter (2024)
This factsheet gives answers on how climate exacerbates root causes of conflict in Zimbabwe, using an climate security pathway analysis. Two main climate security pathway are identified: